A Bioinformatic Analysis of Correlations between Polymeric Immunoglobulin Receptor (PIGR) and Liver Fibrosis Progression. (12th April 2021) - Zhang, Yuan; Lu, Wenjun; Chen, Xiaorong; Cao, Yajuan; Yang, Zongguo
Abstract : Objective . This study is aimed at investigating the enriched functions of polymeric immunoglobulin receptor (PIGR) and its correlations with liver fibrosis stage. Methods . PIGR mRNA expression in normal liver, liver fibrosis, hepatic stellate cells (HSCs), and hepatitis virus infection samples was calculated in Gene Expression Omnibus (GEO) and Oncomine databases. Enrichment analysis of PIGR-related genes was conducted in Metascape and Gene Set Enrichment Analysis (GSEA). Logistic model and ROC curve were performed to evaluate the correlations between pIgR and liver fibrosis. Results . PIGR mRNA was upregulated in advanced liver fibrosis, cirrhosis compared to normal liver (all p < 0.05 ). PIGR mRNA was also overexpressed in activated HSCs compared to senescent HSCs, liver stem/progenitor cells, and reverted HSCs (all p < 0.05 ). Enrichment analysis revealed that PIGR-related genes involved in the defense response to virus and interferon (IFN) signaling. In GEO series, PIGR mRNA was also upregulated by hepatitis virus B, C, D, and E infection (all p < 0.05 ). After adjusting age and gender, multivariate logistic regression models revealed that high PIGR in the liver was a risk factor for liver fibrosis (OR = 82.2, p < 0.001 ). The area under curve (AUC), positive predictive value (PPV), negative predictive value (NPV), sensitivity, and specificity of PIGR for liver fibrosis stage >2 were 0.84, 0.86, 0.7, 0.61, and 0.90. Conclusion . PIGR was correlated with liver fibrosis and might involve in hepatitis virus infection and HSC transdifferentiation.